Very virulent infectious bursal disease virus-induced immune injury is involved in inflammation, apoptosis, and inflammatory cytokines imbalance in the bursa of fabricius. (January 2021) - Huang, Xuewei; Liu, Wei; Zhang, Junyan; Liu, Zengsu; Wang, Meng; Wang, Li; Zhou, Han; Jiang, Yanping; Cui, Wen; Qiao, Xinyuan; Xu, Yigang; Li, Yijing; et al.
Abstract: Infectious bursal disease virus (IBDV) can cause a highly contagious disease in young chickens, resulting in bursal necrosis that causes severe damage to the immune system. The effects of various IBDV strains on the bursa of Fabricius (BF) have been extensively studied; however, few studies have investigated the effects of IBDV strain LJ-5, a newly discovered very virulent IBDV (vvIBDV), infection on young chicken BF. In this study, three-week-old specific pathogen-free (SPF) chickens were infected with vvIBDV for one to five days. LJ-5 decreased the bursa index, B lymphocyte viability and immunoglobulin (Ig) levels, including IgM and IgA in the bursa and IgY in the sera. Histopathological analysis revealed necrosis and depletion of the lymphoid cells and complete loss of bursal architecture in the BF, and transmission electron microscopy revealed mitochondrial vacuoles, cristae breaks, and nuclear damage in vvIBDV-infected bursa tissue. The number of terminal deoxynucleotidyl transferase-mediated dUTP nick end-labeling-positive nuclei significantly increased following IBDV infection. Cytokine levels increased in the bursa after IBDV infection, promoting inflammation and causing an inflammatory imbalance. Apoptotic gene expression confirmed that vvIBDV infection promotes the apoptosis of bursal cells. These results suggest that vvIBDV infection attenuate immune responses by reducing B lymphocyte activity of secretion Ig in the bursa or sera and triggers inflammation, apoptosis, and an imbalance of inflammatory cytokines in the BF, resulting in immune injury in SPF chickens, which offered basic data for further study of vvIBDV pathogenesis. Graphical abstract: Image 1 Highlights: vvIBDV infection affects bursa of Fabricius growth, B lymphocyte viability, and immunoglobulin production. vvIBDV infection induces cytokine expression and inflammatory cytokine imbalance. Apoptosis is an injury mechanism to the bursa of Fabricius caused by vvIBDV. Inflammation is involved in vvIBDV-induced immune injury in SPF chickens. Apoptosis is involved in vvIBDV-induced immune injury in SPF chickens.